The Next Wave in Computing, Optimization, and Decision Technologies - Golden, Bruce L.; Raghavan, S.; Wasil, Edward A. (Operations Research/Computer Science Interfaces Series, 2005)
THE NEXT WAVE IN COMPUTING, OPTIMIZATION, AND DECISION TECHNOLOGIES is divided into six sections. The first section contains two papers on network models. The second section focuses in integer and mixed integer programming. The third section contains papers in which heuristic search and metaheuristics are applied. Three papers using stochastic modeling comprise the fourth section. In the fifth section, the unifying theme is software and modeling. The sixth section contains four papers on classification, clustering, and ranking. Each article in the volume has been carefully reviewed and revised accordingly. Computer Science and Operations Research continue to have a synergistic relationship and this book represents the results of the cross-fertilization between OR/MS and CS/AI. It is this interface of OR/CS that makes possible advances that could not have been achieved in isolation. Taken collectively, these articles are indicative of the state-of-the-art in the interface between OR/MS and CS/AI and of the high-caliber research being conducted by members of the INFORMS Computing Society.